Business information needs and seeking behaviour of tie and dye small and medium scale entrepreneurs (SMEs) - Ochien, Lucy, Mathoro; Mosha, Goodluck E.; Siyao, Peter O. (NAISIT, 2023)
This study investigates the business information needs and seeking behaviour of tie and dye SMSEs in Ilala and Kinondoni Districts in Dar es Salaam, Tanzania. It comprised a sample of 50 respondents who were largely 41(82%) females and only 9(18%) males. It used a cross-sectional design for both quantitative and qualitative research approaches. The data were collected by using structured questionnaires, and face–to–face interviews. The ones collected through questionnaires were summarised and analysed using SPSS and Microsoft Excel Spreadsheet. Data from the in-depth interview were analysed using content analysis. The key findings of the study indicate that: firstly tie and dye SMSE members prefer to seek information through radios, printed materials, television, mobile and landline phones, friends, relatives, neighbours, and business leaders, and by consulting the experienced SMSEs so as to share information. Secondly, the most needed tie and dye information includes market situation, credit availability from financial institutions, information on business risks, sources of raw materials, and information on external market opportunities. Thirdly, the study identified challenges facing the tie and dye SMSEs in seeking information. The challenges were: excessive cost of accessing information, format and language problems, lack of knowledge and skills on how to seek information and inaccessible information sources such as libraries and information centres. The study recommends the presence of accessible libraries and information centres containing relevant and simple information materials written in well-understood languages on the tie and dye business